Effect of the interconnecting window diameter of hydroxyapatite scaffolds on vascularization and osteoinduction. Issue 17 (1st September 2022) - Li, Jinyu; Huang, Hao; Xu, Taotao; Li, Jinsheng; Guo, Tailin; Lu, Xiong; Ren, Jing; Ren, Xiaohua; Mu, Yandong; Weng, Jie
Abstract: The interconnectivity of the scaffold determines oxygen and nutrients transmission, and metabolic waste discharge, which plays a crucial role in cell migration, blood vessel, and tissue regrowth. In the present study, three types of porous hydroxyapatite scaffolds (HAS) with the same pore sizes but different interconnecting window diameters were fabricated by sugar spheres-leaching and heat treatment technique and were used to investigate the effect of interconnecting window diameter on ectopic angiogenesis and osteogenesis. In vitro cell culture experiments showed that the interconnectivity did not influence the performance of cells, whil e in vivo animal experiments revealed that the interconnecting window diameter of HAS impacted not only angiogenesis but also osteogenesis. The mean diameter of blood vessels was increased with the increase of interconnecting window diameter after 4 weeks of implantation, and the sample of mHAS (with about 0.25 w/m ratio of interconnecting window diameter to macro-pore diameter) exhibited the best osteogenesis after 12 weeks of implantation. This study provides a new reference for designing the porous structure of HAS effectively to enhance the new bone formation of bone tissue engineering scaffolds via vascularization in clinic application.